Acute sport-related stressors, coping, and emotion among professional rugby union players during training and matches - Nicholls, A. R.; Jones, C. R.; Polman, R. C. J.; Borkoles, E. (Scandinavian Journal of Medicine & Science in Sports, 2009)
The purpose of this study was to examine acute sport-related stressors, coping, and emotion among a sample of professional rugby union players during training and matches. Five professional rugby union players maintained diaries for 31 days. The diaries consisted of a stressor checklist and an open-ended stressor response section, an open-ended coping response section, a Likert-type evaluation of coping effectiveness, a best-of-fit emotional response section, and a Likert-type evaluation of emotional intensity. Six out of the 10 stressors reported had a higher mean frequency in training compared with matches. Blocking was the most frequently cited coping strategy on match days, whereas increased concentration was the most frequently cited coping strategy on training days. Coping effectiveness was significantly higher during training compared with matches. Additionally, higher levels of emotional intensity were significantly associated with lower levels of coping effectiveness. Significant individual differences were found for both coping effectiveness and emotional intensity.